Strategic Venturing as Legitimacy Creation: The Case of Sustainability - Markus Reihlen; Jan-Florian Schlapfner; Monika Seeger; Hannah Trittin-Ulbrich (Journal of Management Studies, 2021)
Legitimacy is crucial for the survival and growth of strategic ventures inside larger corporations. Yet, despite much progress, research on the strategic venturing-legitimacy nexus, that is, how internal strategic initiatives gain legitimacy and become part of the corporate strategy, remains underexplored. Drawing on the analysis of a longitudinal case study of the development of a sustainability initiative within a major diversified firm, we identified three core mechanisms of legitimation – seeding, energizing and prospering – that turned the concept of sustainability from an internally widely shared moral obligation into a business case. Our study contributes three distinct mechanisms that facilitate the legitimation and the integration of a strategic initiative within the corporate strategy. Moreover, we show how the sequence of legitimation mechanisms matters and highlight the inherently sequenced nature of strategic venture legitimation.
Keywords: 650; strategic venturing; internal corporate venturing; legitimacy; process theory; sustainability; case study